Engineering properties of sand–rubber tire shred mixtures. Issue 9 (21st October 2021) - B.r., Madhusudhan; Boominathan, A.; Banerjee, Subhadeep
ABSTRACT: This study deals with the determination of the engineering properties of sand–rubber tire shred mixtures. The rubber tire shreds of fine size are mixed with river sand in various controlled proportions and tested under dense, fully saturated conditions. The monotonic direct shear tests, one-dimensional compression, and the permeability tests are conducted on these mixtures to determine their shear behaviour, compressibility, and drainage characteristics. The increase in rubber content results in the reduction of shear strength, constrained modulus and the increase of compressibility of the mixtures. The brittleness index which is a measure of ductility and the energy absorption capacity is also discussed. Intriguingly, the permeability of the mixtures reduces with the increase in rubber content. The contact angles of sand-water and the rubber–water interfaces determined using Goniometer explains this behaviour.